LEPTIN RESISTANCE AND ITS ROLE IN THE PATHOPHYSIOLOGY OF OBESITY AND METABOLIC DISORDERS: A LITERATURE REVIEW - Dąbek, Karol; Czyżak, Kamila; Marzec, Urszula; Cyrkler, Aleksandra; Cieślak, Natalia; Chodkowska, Agata; Rajca, Eliza; Giza, Agnieszka; Giza, Paulina; Wymoczył, Karolina (International Journal of Innovative Technologies in Social Science, 2026)
Introduction: Obesity is a global health crisis linked to severe metabolic comorbidities. Leptin, a key hormone regulating energy homeostasis, fails to suppress appetite in obese individuals despite hyperleptinemia—a state known as leptin resistance.Methods: This study presents current knowledge on leptin resistance and its role in obesity and metabolic disorders. A narrative literature review was conducted using PubMed, Scopus, and Web of Science, focusing on recent molecular studies, neuroendocrine mechanisms, and cardiometabolic consequences.Key findings Leptin resistance involves a multi-level failure of the signaling axis, including impaired blood-brain barrier transport, LepRb receptor downregulation, and JAK2-STAT3 cascade disruption. Key molecular drivers include intracellular inhibitors (SOCS3, PTP1B), endoplasmic reticulum (ER) stress, and diet-induced hypothalamic neuroinflammation. This state leads to severe consequences, such as ectopic lipid accumulation, lipotoxicity, and peripheral insulin resistance.Conclusion: Leptin resistance is a central pathogenic mechanism in obesity and metabolic syndrome. Targeting specific molecular blockades through novel leptin sensitizers and incretin-based polypharmacology represents a highly promising frontier for future anti-obesity therapies.